2023
DOI: 10.9734/ajeba/2023/v23i4929
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Marketing Activities (SMMAs) as Stimulus on Purchase Intention with Customer Engagement as Mediator on @avoskinbeauty TikTok’s Account

Abstract: Aims: This research will look at the extent of the influence of Social Media Marketing Activities carried out by Avoskin Beauty to market their products so that potential; consumers are interested in buying products offered by Avoskin Beauty which are mediated by Customer Engagement. Study Design: A quantitative approach used a questionnaire comprising 205 respondents through purposive sampling. Place and Duration of Study: This study was taken place at Pontianak, West Kalimantan with Social Media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although the S-O-R model is commonly cited in hospitality and tourism research (e.g., Daunt & Harris, 2012;Jani & Han, 2015), studies have rarely revealed the mediation effect of CE as a processing mechanism. CE is believed to be conceptually related to one's emotional process as a mediator (Husnain & Toor, 2017). In the S-O-R framework, the organism element represents customers' cognitive and affective states bridging stimuli and responses (Loureiro & Ribeiro, 2014).…”
Section: Customer Engagementmentioning
confidence: 99%
“…Although the S-O-R model is commonly cited in hospitality and tourism research (e.g., Daunt & Harris, 2012;Jani & Han, 2015), studies have rarely revealed the mediation effect of CE as a processing mechanism. CE is believed to be conceptually related to one's emotional process as a mediator (Husnain & Toor, 2017). In the S-O-R framework, the organism element represents customers' cognitive and affective states bridging stimuli and responses (Loureiro & Ribeiro, 2014).…”
Section: Customer Engagementmentioning
confidence: 99%
“…It has been observed that the consumers look forward for gaining the appropriate products that can meet their expectations. It is referred to the perceived value that has a significant positive impact on the consumers according to Husnain and Toor (2017). Perceived value of the consumers are their expectations that are needed to be fulfilled by the marketers by creating such products that can meet consumers' expectations and can make them satisfied with the products offerings are also create trust for the brand (Al-Hawary et al, 2011;Alshurideh et al, 2017;Alolayyan et al, 2018;Al-Hawary & Metabis, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%